Electrode for secondary battery, and secondary battery

By analyzing the active material layer of the secondary battery, the uniform dispersion of the conductive additive is ensured, and the problem of lowering the working voltage under high current density is solved, and low diffusion resistance and high energy efficiency are achieved.

CN119581483APending Publication Date: 2025-03-07HONDA MOTOR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411201522.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-08-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Under high current density, the working voltage of the secondary battery is easily reduced significantly, and the material dispersion of the active material layer is insufficient, resulting in high diffusion resistance.

Method used

By performing Voronoi analysis of the conductive additive as the parent point of the cross-sectional image of the active material layer, the area and standard deviation of the Voronoi region are obtained to ensure that it is within a specific range to achieve uniform dispersion of the conductive additive and low diffusion resistance.

Benefits of technology

The working voltage of the secondary battery under high current density is achieved, and the ion diffusion resistance of the active material layer is reduced, thereby improving energy efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581483A_ABST
    Figure CN119581483A_ABST
Patent Text Reader

Abstract

The problem to be solved by the present invention is to provide: an electrode for a secondary battery having an active material layer in which a material such as an active material and a conductive auxiliary agent is uniformly dispersed and in which the diffusion resistance of ions is low; and a secondary battery having a high operating voltage at a high current density. In order to solve the problem, this electrode for a secondary battery has a current collector and an active material layer disposed on at least one surface of the current collector, the active material layer containing an active material and a conductive auxiliary agent, and the conductive auxiliary agent is formed from an image of a cross-section. The average value of the area of the Voronoi region obtained by Voronoi analysis using the conductive auxiliary agent as the base point is in the range of 1.00 [mu] m2 or more and 2.50 [mu] m2 or less, and the standard deviation of the area of the Voronoi region is 0.20 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode for a secondary battery and a secondary battery. Background Art

[0002] In recent years, research and development of secondary batteries that help improve energy efficiency is being carried out to ensure that more people have access to affordable, reliable, sustainable and advanced energy. The electrodes of secondary batteries generally have a current collector and an active material layer that can absorb and release ions (charge carriers) such as lithium ions. As a method for making an active material layer, a coating method is known. The so-called coating method is a method of applying a slurry for forming an active material layer on a current collector and drying it, wherein the slurry for forming an active material layer is formed by dispersing an active material and a conductive aid, and then a solid electrolyte, a binder, a dispersant and other constituent materials as required in a solvent.

[0003] In order to improve the characteristics of the active material layer produced by the coating method, the materials and composition of the slurry for forming the active material layer have been explored. For example, in order to achieve good dispersibility of the active material and the solid electrolyte in the slurry for forming the active material layer and to fully improve the binding force of the active material layer to the collector, the use of two or more solvents has been explored (Patent Document 1). In order to suppress the aggregation of the conductive auxiliary agent in the slurry for forming the active material layer and improve the dispersibility of the conductive auxiliary agent, the use of a prescribed binder has been explored (Patent Document 2).

[0004] [Prior Technical Literature]

[0005] (Patent Document)

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-82362

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-50017 Summary of the invention

[0008] [Problems to be solved by the invention]

[0009] In addition, in the technology related to secondary batteries, the high potential of the operating voltage at high current density is one of the problems. In order to increase the potential of the operating voltage at high current density, it is effective to reduce the diffusion resistance of the ions in the active material layer of the electrode so that the ions in the active material layer are easily diffused. As a means for reducing the diffusion resistance of the ions in the active material layer, it is generally believed that uniformly dispersing materials such as the active material and the conductive aid of the active material layer is one of the effective means. However, according to the research of the inventors, there is a situation where the dispersibility of the material in the previous active material layer is insufficient, and there is a situation where the operating voltage at high current density is greatly reduced.

[0010] The present invention is made in view of the above problems, and aims to provide an electrode for a secondary battery and a secondary battery with a high operating voltage at a high current density, wherein the electrode for a secondary battery has an active material layer in which materials such as an active material and a conductive additive are uniformly dispersed and the diffusion resistance of ions is low, and further contributes to improving energy efficiency.

[0011] [Technical means to solve the problem]

[0012] The inventors have found that the dispersion (uniformity) of the active material layer can be reasonably grasped by using the area of ​​the Voronoi region obtained by performing Voronoi analysis with the conductive auxiliary agent as the parent point on the image of the cross section of the active material layer and the standard deviation of the area of ​​the Voronoi region. In addition, it was confirmed that in an electrode having an active material layer in which the average value of the area of ​​the Voronoi region and the average value of the standard deviation of the area of ​​the Voronoi region are predetermined values, the diffusion resistance is reduced, and in a secondary battery using the electrode, the operating voltage at a high current density is increased, thereby completing the present invention. Thus, the present invention provides the following invention.

[0013] (1) An electrode for a secondary battery, comprising a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer comprises an active material and a conductive additive, and the average area of ​​a Voronoi region obtained by performing a Voronoi analysis on a cross-sectional image with the conductive additive as a parent point is within 1.00 μm 2 Above and 2.50μm 2 In the following range, the standard deviation of the area of ​​the Voronoi region is 0.20 or less.

[0014] According to the secondary battery electrode of (1), since the average value and standard deviation of the area of ​​the Voronoi region obtained by performing the Voronoi analysis with the conductive auxiliary agent as the parent point are within the above range, the conductive auxiliary agent is uniformly dispersed in the active material layer, so the conductivity of the active material layer is uniform. Therefore, ions are easily diffused throughout the active material layer, and the diffusion resistance of ions in the active material layer is reduced.

[0015] (2) The secondary battery electrode according to (1), wherein the coefficient of variation of the area of ​​the Voronoi region is 10.0% or less.

[0016] According to the secondary battery electrode of (2), since the coefficient of variation of the area of ​​the Voronoi region is within the above range, the diffusion resistance of ions in the active material layer is further reduced.

[0017] (3) The electrode for a secondary battery according to (1) or (2), wherein the conductive aid is spherical, and the ratio of the average particle size of the conductive aid measured by laser diffraction to the average particle size of the active material measured by laser diffraction is within a range of 0.010 to 0.080.

[0018] According to the secondary battery electrode of (3), since the conductive auxiliary agent is spherical and finer than the active material, the conductive auxiliary agent can be easily dispersed uniformly in the active material layer, and thus the diffusion resistance of ions in the active material layer is further reduced.

[0019] (4) An electrode for a secondary battery according to any one of (1) to (3), further comprising a solid electrolyte, wherein the ratio of the average particle size of the solid electrolyte measured by laser diffraction to the average particle size of the active material measured by laser diffraction is within a range of greater than 0.10 and less than 0.90.

[0020] According to the secondary battery electrode of (4), since the solid electrolyte is finer than the active material, the diffusion resistance of ions in the active material layer is further reduced. Therefore, the secondary battery electrode of (4) is useful as an electrode for a solid battery.

[0021] (5) The secondary battery electrode according to any one of (1) to (4), wherein an average particle size of the active material measured by laser diffraction is within a range of 1.0 μm to 5.0 μm.

[0022] According to the secondary battery electrode of (5), since the average particle size of the active material is fine and within the above range, the surface area of ​​the active material is large, and therefore the diffusion resistance of ions in the active material layer is further reduced.

[0023] (6) The secondary battery electrode according to any one of (1) to (5), which is used as a positive electrode of a secondary battery.

[0024] The secondary battery electrode according to (6) is useful as a positive electrode of a solid battery or a nonaqueous solvent secondary battery.

[0025] (7) A secondary battery comprising the secondary battery electrode according to any one of (1) to (6).

[0026] According to the secondary battery of (7), since the secondary battery includes the above-mentioned secondary battery electrode, the decrease in the operating voltage at a high current density is reduced, and the operating voltage at a high current density is increased.

[0027] (Effects of the Invention)

[0028] According to the present invention, there can be provided a secondary battery electrode having an active material layer in which materials such as an active material and a conductive additive are uniformly dispersed and ion diffusion resistance is low, and a secondary battery having a high operating voltage at a high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a cross-sectional view showing a secondary battery according to one embodiment of the present invention.

[0030] Figure 2 This is a schematic diagram showing an example of a Voronoi diagram obtained by performing Voronoi analysis using a conductive auxiliary agent as a parent point on a cross section of a positive electrode active material layer of a secondary battery according to an embodiment of the present invention.

[0031] Figure 3A This is a secondary electron image of a cross section of the positive electrode active material layer obtained in Example 1.

[0032] Figure 3B This is a Voronoi plot of the cross section of the positive electrode active material obtained in Example 1, with the conductive additive as the parent point.

[0033] Figure 4A This is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Example 1.

[0034] Figure 4B Graph 1 is a frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Example 2.

[0035] Figure 4C This is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Example 3.

[0036] Figure 4D This is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Example 4.

[0037] Figure 4E This is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Comparative Example 1.

[0038] Figure 4F This is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Comparative Example 2.

[0039] Figure 4GThis is the frequency distribution of the average area of ​​the Voronoi domain measured at 30 locations in the cross section of the positive electrode active material layer obtained in Comparative Example 3.

[0040] Figure 5 This is a graph showing IV characteristics of solid batteries produced using the positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0041] Hereinafter, a secondary battery electrode according to an embodiment of the present invention and a secondary battery using the electrode will be described in detail with reference to the drawings, but the present invention is not limited thereto.

[0042] Figure 1 is a cross-sectional view showing a secondary battery according to one embodiment of the present invention. Figure 2 This is a schematic diagram showing an example of a Voronoi diagram obtained by performing Voronoi analysis using a conductive auxiliary agent as a parent point on a cross section of a positive electrode active material layer of a secondary battery according to an embodiment of the present invention.

[0043] like Figure 1 As shown, the secondary battery 1 of the present embodiment is a solid battery including an electrode stack 10 and a package 50 that houses the electrode stack 10 .

[0044] The electrode stack 10 is a stack formed by stacking a positive electrode 20 and a negative electrode 30 via a solid electrolyte layer 40. The positive electrode 20 includes a positive electrode collector 21 and a positive electrode active material layer 22 disposed on the surface of the positive electrode collector 21 on the solid electrolyte layer 40 side. The positive electrode collector 21 is connected to a positive electrode terminal 24 via a positive electrode lead 23. The negative electrode 30 includes a negative electrode collector 31 and a negative electrode active material layer 32 disposed on the surface of the negative electrode collector 31 on the solid electrolyte layer 40 side. The negative electrode collector 31 is connected to a negative electrode terminal 34 via a negative electrode lead 33. A portion of the positive electrode terminal 24 and the negative electrode terminal 34 are exposed from the package 50.

[0045] The positive electrode current collector 21 is not particularly limited in material and shape as long as it has the function of collecting current for the positive electrode 20. Examples of the material of the positive electrode current collector 21 include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium, among which aluminum, aluminum alloys, and stainless steel are preferred. In addition, examples of the shape of the positive electrode current collector 21 include foil, plate, and the like.

[0046] The positive electrode active material layer 22 is Figure 2 As shown, in the Voronoi diagram obtained by performing a Voronoi analysis with the conductive auxiliary agent 221 as the parent point, the average value of the area of ​​the Voronoi region 222 is 1.00 μm 2 Above and 2.50μm 2In the following range, the standard deviation of the area of ​​the Voronoi region 222 is less than 0.20. The average value of the area of ​​the Voronoi region 222 represents the distance between the conductive aids 221 and the conductive aids 221. The standard deviation of the area of ​​the Voronoi region 222 represents the unevenness of the distance between the conductive aids 221 and the conductive aids 221. Therefore, if the average value and the standard deviation of the area of ​​the Voronoi region 222 are within the above range, the conductive aid 221 will be uniformly dispersed in the positive electrode active material layer 22. The average value of the area of ​​the Voronoi region 222 can also be within 1.50 μm 2 Above and 2.00μm 2 The standard deviation of the area of ​​the Voronoi region 222 may be in the range of 0.05 to 0.20. The coefficient of variation of the area of ​​the Voronoi region 222 may be 10.0% or less, or may be in the range of 1.0% to 9.0% or less.

[0047] The Voronoi diagram can be obtained, for example, as follows. For the cross section of the positive electrode active material layer 22, an electron reflection image is obtained using a scanning electron microscope (SEM). The obtained electron reflection image is binarized with the area of ​​the conductive auxiliary agent that does not reflect electrons and the other area that reflects electrons. The area of ​​the conductive auxiliary agent in the obtained binary image is used as the parent point, and Voronoi analysis is performed to obtain the Voronoi diagram.

[0048] The positive electrode active material layer 22 includes at least one positive electrode active material and a conductive additive.

[0049] The positive electrode active material is not particularly limited, and for example, a layered active material containing lithium, a spinel type active material, an olivine type active material, etc. can be used. Specific examples of positive electrode active materials include: lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 )、LiNi p Mn q Co r O 2 (p+q+r=1), LiNi p Al q Co r O 2 (p+q+r=1), lithium manganate (LiMn 2 O 4 ) 1+x Mn 2-x-y MO 4(x+y=2, M is selected from at least one of Al, Mg, Co, Fe, Ni and Zn) represented by a heterogeneous element substituted Li-Mn spinel, lithium titanate (an oxide containing Li and Ti), lithium metal phosphate (LiMPO 4 , M is selected from at least one of Fe, Mn, Co and Ni).

[0050] The shape of the positive electrode active material can be, for example, spherical, polyhedral, or has no fixed shape. The spherical shape does not have to be a sphere, and the aspect ratio can be 2 or less. The average particle size (D50) of the positive electrode active material can also be in the range of 1.0 μm to 6.5 μm. In addition, in the positive electrode active material, the particle size (D90) at which the cumulative particle size distribution under the sieve is 90% can also be in the range of 5.5 μm to 10.0 μm. Furthermore, the ratio D90 / D50 of the D90 of the positive electrode active material to D50 can also be in the range of 1.3 to 1.9. In addition, in the present embodiment, the particle size is a value measured by a laser diffraction method.

[0051] There is no particular limitation on the conductive aid, and for example, conductive carbon can be used. The shape of the conductive aid can be, for example, spherical. As the spherical conductive carbon, carbon black can be used. The average particle size of the conductive aid, measured as the ratio of the average particle size of the conductive aid to the average particle size of the active material (average particle size of the conductive aid / average particle size of the active material), can also be in the range of 0.010 to 0.080. The average particle size (D50) of the conductive aid can also be in the range of 0.010 μm to 0.50 μm. In addition, in the conductive aid, the particle size (D90) at which the cumulative particle size distribution under the sieve is 90% can also be in the range of 0.3 μm to 1.0 μm. Furthermore, the ratio D90 / D50 of the conductive aid D90 to D50 can also be in the range of 0.6 to 100.

[0052] The positive electrode active material layer 22 may further contain a solid electrolyte, a binder, and a dispersant.

[0053] As the solid electrolyte, the substance used in the solid electrolyte layer 40 can be used.

[0054] The shape of the solid electrolyte contained in the positive electrode active material layer 22 can be, for example, spherical, polyhedral, or has no fixed shape. The average particle size of the solid electrolyte can be in the range of 0.10 to 0.90, measured as the ratio of the average particle size of the solid electrolyte to the average particle size of the active material (average particle size of the solid electrolyte / average particle size of the active material). The average particle size (D50) of the solid electrolyte can also be in the range of 0.50 μm to 1.5 μm. In addition, in the solid electrolyte, the particle size (D90) with a cumulative particle size distribution of 90% under the sieve can also be in the range of 1.5 μm to 3.0 μm. Furthermore, the ratio D90 / D50 of the D90 of the solid electrolyte to D50 can also be in the range of 1.0 to 4.5. Regarding the solid electrolyte contained in the positive electrode active material layer 22, part or all of it can also be coated on the surface of the positive electrode active material.

[0055] The binder is not particularly limited, and for example, fluororesins and rubbers can be used. Examples of fluororesins include polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). Examples of rubbers include styrene butadiene rubber (SBR) and ethylene propylene diene rubber (EPDM).

[0056] The dispersant is not particularly limited, and for example, polyvinyl butyral, polyvinyl pyrrolidone, or carboxymethyl cellulose can be used.

[0057] The content of each material of the positive electrode active material layer 22, for example, the total amount is set to 100 mass%, the content of the active material can be in the range of 50 mass% to 90 mass%, the content of the conductive auxiliary agent can be in the range of 10 mass% to 50 mass%, the content of the solid electrolyte can be in the range of 0 mass% to 40 mass%, the content of the binder can be in the range of 0 mass% to 5 mass%, and the content of the dispersant can be in the range of 0 mass% to 1 mass%. The content of the solid electrolyte can also be in the range of 5 mass% to 40 mass%, the content of the binder can also be in the range of 1 mass% to 5 mass%, and the content of the dispersant can also be in the range of 0.05 mass% to 1 mass%.

[0058] The positive electrode active material layer 22 can be manufactured by applying a slurry for forming a positive electrode active material layer on the surface of the positive electrode collector 21 and drying it. The slurry for forming a positive electrode active material layer can be prepared, for example, as follows. First, a binder-containing liquid is prepared. The binder-containing liquid can be obtained by dissolving or dispersing the binder in a solvent. As a solvent, an ester solvent can be used. As an example of an ester solvent, butyl butyrate can be cited. Then, a conductive auxiliary agent and a dispersant are added to the binder-containing liquid and mixed. Then, an active material and a solid electrolyte are added to the binder-containing liquid to which a conductive auxiliary agent and a dispersant are added, and mixed. Mixing can be performed using a ball mill, for example.

[0059] The material of the positive electrode lead 23 may be the same as or different from that of the positive electrode current collector 21. The positive electrode lead 23 may be integrally connected to the positive electrode current collector 21. The material of the positive electrode terminal 24 may be the same as or different from that of the positive electrode lead 23. The positive electrode terminal 24 may be integrally connected to the positive electrode lead 23.

[0060] The negative electrode current collector 31 is not particularly limited in material and shape as long as it has the function of collecting current for the negative electrode 30. Examples of the material of the negative electrode current collector 31 include nickel, copper, and stainless steel. In addition, examples of the shape of the negative electrode current collector 31 include foil, plate, and the like.

[0061] The negative electrode active material layer 32 contains at least one negative electrode active material.

[0062] As the negative electrode active material, a substance capable of absorbing and releasing lithium ions or a metal that forms an alloy with lithium can be used. As the substance capable of absorbing and releasing lithium ions, for example, lithium titanate (Li 4 Ti 5 O 12 ) and other lithium transition metal oxides, TiO 2 , Nb 2 O 3 and WO 3 Examples of the metal that can form an alloy with lithium include transition metal oxides, metal sulfides, metal nitrides, graphite, soft carbon, and hard carbon. Examples of the metal that can form an alloy with lithium include Mg, Si, Au, Ag, In, Ge, Sn, Pb, Al, and Zn.

[0063] The shape of the negative electrode active material can be, for example, spherical, polyhedral, or have no fixed shape. The average particle size (D50) of the negative electrode active material can also be in the range of 1.0 μm or more and 5.0 μm or less. In addition, in the negative electrode active material, the particle size (D90) at which the cumulative particle size distribution under the sieve is 90% can also be in the range of 5.5 μm or more and 7.0 μm or less. Furthermore, the ratio D90 / D50 of the D90 of the negative electrode active material to D50 can also be in the range of 1.3 or more and 1.9 or less.

[0064] The negative electrode active material layer 32 may further contain a conductive additive, a solid electrolyte, a binder, and a dispersant. The conductive additive, the solid electrolyte, the binder, and the dispersant may be the same as those exemplified for the positive electrode active material layer 22 .

[0065] The material of the negative electrode lead 33 may be the same as or different from the material of the negative electrode current collector 31. The negative electrode lead 33 may be integrally connected to the negative electrode current collector 31. The material of the negative electrode terminal 34 may be the same as or different from the material of the negative electrode lead 33. The negative electrode terminal 34 may be integrally connected to the negative electrode lead 33.

[0066] The solid electrolyte layer 40 contains at least one solid electrolyte material. As the solid electrolyte material, for example, a sulfide solid electrolyte material, an oxide solid electrolyte material, a nitride solid electrolyte material, a halide solid electrolyte material, or the like can be used.

[0067] Examples of sulfide solid electrolyte materials include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 6 PS 5 Cl, Li 3 PS 4 In addition, the above “Li 2 SP 2 S 5 " refers to the use of Li 2 S and P 2 S 5 The sulfide solid electrolyte material may also have an argyrodite-type crystal structure.

[0068] Examples of oxide solid electrolyte materials include sodium superionic conductor (NASICON) type oxides, garnet type oxides, and perovskite type oxides. Examples of NASICON type oxides include oxides containing Li, Al, Ti, P, and O (e.g., Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 As examples of garnet-type oxides, oxides containing Li, La, Zr, and O (e.g., Li 7 La 3 Zr 2 O 12 As examples of perovskite-type oxides, oxides containing Li, La, Ti, and O (e.g., LiLaTiO 3 ).

[0069] The shape of the solid electrolyte contained in the solid electrolyte layer 40 can be, for example, spherical, polyhedral, or non-fixed. The average particle size (D50) of the solid electrolyte can also be in the range of 3.0 μm or more and 5.0 μm or less. In addition, in the solid electrolyte, the particle size (D90) at which the cumulative particle size distribution under the sieve is 90% can also be in the range of 5.0 μm or more and 10.0 μm or less. Furthermore, the ratio D90 / D50 of the D90 of the solid electrolyte to D50 can also be in the range of 1.5 or more and 3.5 or less.

[0070] As a material of the package body 50, for example, a laminated film can be used. As the laminated film, a laminated film having a three-layer structure in which an inner resin layer, a metal layer, and an outer resin layer are sequentially laminated from the inner side can be used. The outer resin layer can be, for example, a polyamide (nylon) layer or a polyethylene terephthalate (PET) layer, the metal layer can be, for example, an aluminum layer, and the inner resin layer can be, for example, a polyethylene layer or a polypropylene layer.

[0071] The secondary battery 1 of the present embodiment can be manufactured, for example, as follows.

[0072] First, the positive electrode 20, the solid electrolyte layer 40, and the negative electrode 30 are sequentially stacked, and the obtained stack is press-bonded to obtain the electrode stack 10. The electrode stack 10 may be pressurized in the stacking direction to improve the adhesion of the positive electrode 20, the solid electrolyte layer 40, and the negative electrode 30, and to increase the density of the positive electrode active material layer 22 and the negative electrode active material layer 32. Next, the positive terminal 24 is connected to the positive electrode collector 21 of the electrode stack 10 via the positive electrode lead 23, and the negative terminal 34 is connected to the negative electrode collector 31 via the negative electrode lead 33. Next, the electrode stack 10 is housed in the package 50, and the package 50 is sealed.

[0073] According to the secondary battery 1 of the present embodiment having the above structure, the average value and standard deviation of the area of ​​the Voronoi region 222 obtained by performing a Voronoi analysis with the conductive agent 221 as the parent point on the image of the cross section of the positive electrode active material layer 22 are within the above range, and the conductive agent is uniformly dispersed in the positive electrode active material layer 22, so the conductivity of the positive electrode active material layer 22 is uniform. Therefore, ions are easily diffused throughout the positive electrode active material layer 22, and the diffusion resistance of ions in the positive electrode active material layer 22 is reduced. As a result, the operating voltage of the secondary battery 1 at a high current density is increased.

[0074] In the secondary battery 1 of the present embodiment, when the coefficient of variation of the area of ​​the Voronoi region 222 is within the above range, the diffusion resistance of the ions in the positive electrode active material layer 22 is further reduced, so the operating voltage at a high current density of the secondary battery 1 is further increased. In the secondary battery 1 of the present embodiment, the conductive aid of the positive electrode active material layer 22 is spherical, and when the ratio of the average particle size of the conductive aid to the average particle size of the positive electrode active material (the average particle size of the conductive aid / the average particle size of the positive electrode active material) is within the above range, it is easier to evenly disperse the conductive aid in the positive electrode active material layer 22, and the diffusion resistance of the ions in the positive electrode active material layer 22 is further reduced. Therefore, the operating voltage at a high current density of the secondary battery 1 is further increased. In the secondary battery 1 of the present embodiment, the positive electrode active material layer 22 also includes a solid electrolyte, and when the ratio of the average particle size of the solid electrolyte to the average particle size of the positive electrode active material (the average particle size of the solid electrolyte / the average particle size of the positive electrode active material) is within the above range, the diffusion resistance of the ions in the positive electrode active material layer 22 is further reduced. Therefore, the operating voltage of the secondary battery 1 at a high current density becomes higher. In the secondary battery 1 of this embodiment, the average particle size of the positive electrode active material is fine, and when it is within the above range, the surface area of ​​the active material is large, and the diffusion resistance of the ions in the positive electrode active material layer is further reduced. Therefore, the operating voltage of the secondary battery 1 at a high current density becomes higher.

[0075] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment.

[0076] For example, in the secondary battery 1 of the present embodiment, the average value of the area of ​​the Voronoi region with the conductive auxiliary agent of the positive electrode active material layer 22 as the parent point and the standard deviation of the area of ​​the Voronoi region are within the above range, but the structure of the electrode is not limited thereto. For example, in the case where the negative electrode active material layer 32 contains the negative electrode active material and the conductive auxiliary agent, the average value of the area of ​​the Voronoi region obtained by performing a Voronoi analysis with the conductive auxiliary agent as the parent point on the image of the cross section of the negative electrode active material layer 32 and the standard deviation of the area of ​​the Voronoi region can also be within the above range.

[0077] In the secondary battery 1 of the present embodiment, a structure is adopted in which a negative electrode active material layer 32 is arranged on the surface of the negative electrode collector 31 of the negative electrode 30, lithium ions are absorbed by the negative electrode active material during charging, and lithium ions are released from the negative electrode active material during discharge, but the structure of the negative electrode 30 is not limited thereto. A structure may also be adopted in which no negative electrode active material layer 32 is arranged, lithium ions are deposited on the surface of the negative electrode collector 31 during charging, and lithium ions are released from the deposited lithium during discharge. In this structure, in order to facilitate the deposition of lithium ions on the surface of the negative electrode collector 31 during charging, a lithium foil may be arranged on the surface of the negative electrode collector 31.

[0078] Furthermore, the secondary battery 1 of the present embodiment is a solid battery, and may be a non-aqueous solvent battery. In the case of a non-aqueous solvent battery, the electrolyte is not particularly limited, and various electrolytes used in non-aqueous solvent batteries may be used.

[0079] [Example]

[0080] (Example 1)

[0081] (1) Preparation of coated positive electrode active material

[0082] As the positive electrode active material, Li(NiCoMn) was prepared. x O 2 (x=0.33) (D50: 3.4 μm, D90: 5.3 μm, D90 / D50: 1.56). Li 6 PS 5 Cl (D50: 0.6 μm, D90: 1.5 μm, D90 / D50: 2.5) The positive electrode active material and the solid electrolyte were mixed at a mass ratio of 90:10 to prepare a coated positive electrode active material in which the surface of the positive electrode active material was coated with the solid electrolyte.

[0083] (2) Preparation of slurry for forming positive electrode active material layer

[0084] An SBR (styrene butadiene rubber) adhesive was dissolved in a butyl butyrate solvent to prepare an SBR adhesive solution with a concentration of 10% by mass. 2.63 g of the obtained SBR adhesive solution was weighed, and 4.31 g of the butyl butyrate solvent, 0.79 g of carbon black (spherical carbon, average diameter: 0.1 μm) as a conductive aid, and 0.05 g of PVB (polyvinyl butyral) as a dispersant were added to the SBR adhesive solution. The obtained mixed solution was subjected to a first dispersion treatment, which was: using a self-rotating revolution type mixer (Reintarou ARE310, manufactured by Thinky Co., Ltd.), mixing at 2000 rpm for 10 minutes.

[0085] Into the mixed solution after the first dispersion treatment, 47.6 g of zirconium oxide balls (diameter: 2 mm) and 33.3 g of the coated positive electrode active material obtained in (1) above were added, and then 1.9 g of butyl butyrate solvent was added in such a way that the solid content ratio in the mixed solution became 80.1% by mass. Thereafter, the mixed solution was subjected to two second dispersion treatments, namely, mixing at 2000 rpm for 1 minute using a self-rotating revolution type mixer.

[0086] Into the mixed solution after the second dispersion treatment, 3.06 g of the solid electrolyte prepared in (1) above was added, and the positive electrode active material content was adjusted to 80.0 mass%, the solid electrolyte content was adjusted to 17.1 mass%, the conductive auxiliary agent content was adjusted to 2.1 mass%, the binder content was adjusted to 0.7 mass%, and the dispersant content was adjusted to 0.1 mass%. Then, 1.4 g of butyl butyrate solvent was added so that the solid content ratio in the mixed solution became 79.0 mass%. After that, the mixed solution was subjected to a third dispersion treatment, namely, mixing at 2000 rpm for 2 minutes using a self-rotating revolution mixer.

[0087] After the third dispersion treatment, 4.6 g of butyl butyrate solvent was added to the mixed solution so that the solid content ratio in the mixed solution became 72.0% by mass. Then, the mixed solution was subjected to a fourth dispersion treatment, which was kneading at 2000 rpm for 2 minutes using a rotation and revolution type stirrer.

[0088] After the fourth dispersion treatment, 0.9 g of butyl butyrate solvent was added to the mixed solution so that the solid content ratio in the mixed solution became 70.8% by mass. Thereafter, the mixed solution was subjected to a fifth dispersion treatment, which was kneading at 2000 rpm for 2 minutes using a rotation-revolution type stirrer.

[0089] The mixed solution after the fifth dispersion treatment was filtered using a sieve with a mesh size of 100 μm to remove the zirconium oxide balls. The obtained filtrate was used as a slurry for forming a positive electrode active material layer.

[0090] (3) Preparation of positive electrode

[0091] As a positive electrode current collector, an Al current collector foil was prepared. On the surface of the positive electrode current collector, the slurry for forming a positive electrode active material layer obtained in (2) above was applied and dried to form a positive electrode active material layer. 2 The obtained positive electrode active material layer is pressurized with a pressure of.

[0092] (Example 2)

[0093] In (1) the preparation of the coated positive electrode active material and (2) the preparation of the slurry for forming the positive electrode active material layer, Li 6 PS 5 A positive electrode was produced in the same manner as in Example 1 except that Cl (D50: 1.0 μm, D90: 3.0 μm, D90 / D50: 3.0) was used as the solid electrolyte.

[0094] (Example 3)

[0095] In (1) the preparation of the coated positive electrode active material and (2) the preparation of the slurry for forming the positive electrode active material layer, Li 6 PS 5 Cl (D50: 3.0 μm, D90: 8.0 μm, D90 / D50: 2.7) was used as a solid electrolyte. In the preparation of (2) a slurry for forming a positive electrode active material layer, the solid electrolyte was added to the mixed solution in such a manner that the positive electrode active material content was 60.0 mass %, the solid electrolyte content was 36.0 mass %, the conductive aid content was 2.8 mass %, the binder content was 1.0 mass %, and the dispersant content was 0.2 mass %. Except for this, a positive electrode was prepared in the same manner as in Example 1.

[0096] (Example 4)

[0097] In (2) the preparation of the slurry for forming the positive electrode active material layer, a positive electrode was prepared in the same manner as in Example 1 except that a 10 mass % PVDF binder dispersion prepared by dispersing the PVDF binder in a butyl butyrate solvent was used instead of the SBR binder solution.

[0098] (Comparative Example 1)

[0099] In (1) the preparation of the coated positive electrode active material and (2) the preparation of the slurry for forming the positive electrode active material layer, Li 6 PS5 A positive electrode was produced in the same manner as in Example 1 except that Cl (D50: 3.0 μm, D90: 8.0 μm, D90 / D50: 2.7) was used as the solid electrolyte.

[0100] (Comparative Example 2)

[0101] A positive electrode was prepared in the same manner as in Example 1 except that multiwalled carbon nanotubes (fibrous carbon, average diameter in the long-side direction: 1.0 μm) were used as a conductive additive in (2) preparation of a positive electrode active material layer-forming slurry.

[0102] (Comparative Example 3)

[0103] In (1) the preparation of the coated positive electrode active material and (2) the preparation of the slurry for forming the positive electrode active material layer, Li 3 PS 4 (D50: 1.1 μm, D90: 15.0 μm, D90 / D50: 13.6) A positive electrode was produced in the same manner as in Example 1 except that the solid electrolyte was used.

[0104] (Components of Positive Electrode Active Material Layer)

[0105] The composition of the positive electrode active material layer of the positive electrode obtained as described above and the particle size of each material are summarized and shown.

[0106] [Table 1]

[0107]

[0108] [evaluate]

[0109] The Voronoi analysis of the positive electrode active material layer of the positive electrode obtained in Examples 1 to 4 and Comparative Examples 1 to 3 and the diffusion resistance value of the secondary battery using the positive electrode were measured by the following method. The results are shown in Table 2 below together with the ratio of the average particle size of the conductive auxiliary agent to the average particle size of the positive electrode active material (D50 of the conductive auxiliary agent / D50 of the positive electrode active material) and the ratio of the average particle size of the solid electrolyte to the average particle size of the positive electrode active material (D50 of the solid electrolyte / D50 of the positive electrode active material).

[0110] (Voronoi analysis)

[0111] The positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were cut in the thickness direction. Using FE-SEM (field emission scanning electron microscope JSM-7001F, manufactured by JEOL Ltd.), the field of view was 1044 μm 2The cross section of the positive electrode active material layer was observed under the conditions of (29 μm in length × 36 μm in width, 3000 times). The reflected electron image of the positive electrode active material layer was subjected to a Voronoi analysis with the conductive additive as the parent point. The average area, standard deviation and coefficient of variation of the Voronoi region obtained by the Voronoi analysis were calculated. The cross section observation was performed on 30 sites, and the average area, standard deviation and coefficient of variation of the Voronoi region were calculated for each of the 30 sites.

[0112] For the positive electrode active material obtained in Example 1, Figure 3A The secondary electron image of FE-SEM is shown in Figure 3B The Voronoi diagram is shown in Figure 4A 1 to 4 show the frequency distribution of the average area of ​​the Voronoi region with the conductive additive as the parent point in one image measured at 30 locations of the cross section of the positive electrode active material layer obtained in Examples 1 to 4 and Comparative Examples 1 to 3. Table 2 shows the average area, standard deviation value and average value of the coefficient of variation of the Voronoi region measured at 30 locations.

[0113] (Diffusion resistance value)

[0114] 100 mg of solid electrolyte was measured at 1.5 tons / cm 2 The solid electrolyte particles were obtained by applying a molding pressure of 3.0 tons / cm. The positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were arranged on one side of the solid electrolyte particles. 2 Temporary molding is performed and then 10.0 tons / cm 2 A Li metal plate (1 mm thick) was placed on the opposite side of the solid electrolyte particle to the positive electrode as the negative electrode, and a pressure of 1.5 tons / cm was applied. 2 The stacked body with negative electrode, solid electrolyte particles and positive electrode was obtained by molding under a molding pressure of 10 MPa. Terminals were installed on the positive and negative electrodes of the obtained stacked body via leads. After that, the stacked body was placed in a package with the terminals exposed from the package and sealed to produce a solid battery. Under a restraining pressure of 10 MPa and a test environment of 25°C, the solid battery was tested at 0.1C (1C = 4.0 mA / cm 2 ) current density, the solid battery was charged and discharged. The solid battery after charge and discharge was charged again and discharged until the capacity became 50% (State of Charge (SOC) 50%) relative to the initial discharge capacity, and then the DC resistance and AC impedance of the solid battery were measured. In the DC resistance measurement, the current density (mA / cm2 ) and potential (V) to form an IV characteristic graph, and the DC resistance value is obtained from the slope of the plot of the IV characteristic graph. Figure 5 The IV characteristic diagram is shown in FIG. In the AC impedance measurement, the solid electrolyte resistance value and the positive electrode reaction resistance value (charge transfer resistance value) are obtained according to the amplitude of 1 Hz-1 MHz at an AC voltage of 10 mV. The solid electrolyte resistance value and the positive electrode reaction resistance value obtained in the AC impedance measurement are subtracted from the DC resistance value obtained in the DC resistance measurement, and the obtained value is used as the diffusion resistance value.

[0115] [Table 2]

[0116]

[0117] right Figure 4A ~D and Figure 4E From the comparison of 1 to 4, it can be seen that the frequency distribution of the average area of ​​the Voronoi region of the positive electrode active material layer of Examples 1 to 4 is narrower than the frequency distribution of the average area of ​​the Voronoi region of the positive electrode active material layer of Comparative Examples 1 to 3, and the variation of the average area of ​​the Voronoi region is small.

[0118] According to the results in Table 2, the positive electrode active material layers of Examples 1 to 4, whose average area and standard deviation of the Voronoi region are within the range of the present invention, have smaller diffusion resistance values ​​and ions are easily diffused than the positive electrode active material layers of Comparative Examples 1 to 3, whose average area and standard deviation of the Voronoi region are larger than the range of the present invention. Figure 5 From the IV characteristic graph, it can be seen that the solid batteries made using the positive electrodes obtained in Examples 1 to 4 have a higher operating voltage at a high current density than the solid batteries made using the positive electrodes obtained in Comparative Examples 1 to 3. This is because ions are easily diffused in the positive electrode active material layers of Examples 1 to 4, and the resistance is not easy to increase even when discharged at a high current density.

[0119] Reference numerals

[0120] 1 Secondary battery

[0121] 10-electrode stack

[0122] 20 positive electrode

[0123] 21Positive electrode collector

[0124] 22Positive electrode active material layer

[0125] 23 positive lead

[0126] 24 Positive terminal

[0127] 30 negative electrode

[0128] 31 negative electrode collector

[0129] 32 Negative electrode active material layer

[0130] 33 Negative lead

[0131] 34 Negative terminal

[0132] 36 Lithium precipitation layer

[0133] 40Solid electrolyte layer

[0134] 50 packing

[0135] 221 conductive additive

[0136] 222 Voronoi Area

Claims

1. An electrode for a secondary battery, comprising a current collector and an active material layer disposed on at least one surface of the current collector, The active material layer includes an active material and a conductive additive. The average area of ​​the Voronoi region obtained by performing a Voronoi analysis on the cross-sectional image with the conductive additive as the parent point is 1.00 μm. 2 Above and 2.50μm 2 In the following range, the standard deviation of the area of ​​the Voronoi region is 0.20 or less.

2. The secondary battery electrode according to claim 1, wherein The coefficient of variation of the area of ​​the Voronoi region is 10.0% or less.

3. The secondary battery electrode according to claim 1, wherein The conductive additive is spherical. The ratio of the average particle size of the conductive auxiliary agent measured by laser diffraction to the average particle size of the active material measured by laser diffraction is within a range of 0.010 to 0.

080.

4. The secondary battery electrode according to claim 1, further comprising a solid electrolyte, The ratio of the average particle size of the solid electrolyte measured by laser diffraction to the average particle size of the active material measured by laser diffraction is within a range of 0.10 to 0.

90.

5. The secondary battery electrode according to claim 1, wherein The average particle size of the active material measured by laser diffraction is within a range of 1.0 μm to 5.0 μm. The secondary battery electrode according to claim 1 , which is used as a positive electrode of a secondary battery. 7 . A secondary battery comprising the secondary battery electrode according to claim 1 .

Citation Information

Patent Citations

  • Binder resin for secondary battery electrodes, binder resin composition for secondary battery electrodes, electrode slurry, electrode for secondary batteries, and lithium ion secondary battery

    JP2015050017A

  • Electrode slurry for all-solid batteries, and method for manufacturing electrode for all-solid batteries

    JP2015082362A